Burn center function during the COVID-19 pandemic: An international multi-center report of strategy and experience. Issue 5 (August 2020) - Barret, Juan P.; Chong, Si Jack; Depetris, Nadia; Fisher, Mark D.; Luo, Gaoxing; Moiemen, Naiem; Pham, Tam; Qiao, Liang; Wibbenmeyer, Lucy; Matsumura, Hajime
Highlights: Seven burn units from America, Europe, and Asia describe coping with COVID-19. Critical care scarcity under pandemic conditions produces burn care austerity. Cohorting of staff and patients preserves working units and contains disease. Abstract: The novel coronavirus, SARS-CO V2 responsible for COVID-19 pandemic is rapidly escalating across the globe. Burn centers gearing for the pandemic must strike a balance between contributing to the pandemic response and preserving ongoing burn care in a safe and ethical fashion. The authors of the present communication represent seven burn centers from China, Singapore, Japan, Italy, Spain, the United Kingdom (UK), and the United States (US). Each center is located at a different point along the pandemic curve and serves different patient populations within their healthcare systems. We review our experience with the virus to date, our strategic approach to burn center function under these circumstances, and lessons learned. The purpose of this communication is to share experiences that will assist with continued preparations to help burn centers advocate for optimum burn care and overcome challenges as this pandemic continues.